Windows of the Widow: Re-Seeing the Patriarchal Traps from a Personal Discourse Lens of the Novel 'Divortiare' - Astari, Ranitania Yohana (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2021)
The patriarchal perspective is deeply embedded in Indonesian culture, including popular culture. This issue is an inexhaustible inspiration to be explored in dismantling patriarchal modes, tracing their consequences, and presenting ideas of rebellion and criticism through popular culture narrative content, including pop literature. This article analyzes the personal discourse of the main character in a pop urban women's novel (known as 'chicklit') entitled Divortiare with a Foucauldian discourse analysis (FDA) approach, which focuses on how power relations operate by highlighting the statements that form the subject of discourse, technology/ strategy, and apparatus. The inner struggle of a widow amid a patriarchal cultural circle becomes the subject of personal discourse. This study is the first to analyze the personal discourse of widows in popular literature (read: pop fiction) in the context of patriarchal culture with a Foucauldian approach: how the main character, personally and counter-discursively, fights against extreme patriarchal power.